2022
DOI: 10.3324/haematol.2022.280996
|View full text |Cite
|
Sign up to set email alerts
|

Oral HDAC inhibitor tucidinostat in patients with relapsed or refractory peripheral T-cell lymphoma: phase IIb results

Abstract: Tucidinostat (formerly known as chidamide) is an orally available, novel benzamide class of histone deacetylase (HDAC) inhibitor that selectively blocks class I and class IIb HDACs. This multicenter phase IIb study aimed to investigate the efficacy and safety of tucidinostat, 40 mg twice per week (BIW), in patients with relapsed/refractory (R/R) peripheral T-cell lymphoma (PTCL). The primary endpoint was overall response rate (ORR) assessed by an independent overall efficacy review committee. Between March 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
(77 reference statements)
1
12
0
Order By: Relevance
“… 45 , 46 Specifically, these inhibitors have received approval for treating various hematopoietic cancers, such as cutaneous T‐cell lymphomas. 47 Our findings support the utility of HDAC2 inhibitors in colorectal treatment. SCA, a powerful and specific HDAC2 inhibitor, has been demonstrated to effectively suppresses tumour progression both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 75%
“… 45 , 46 Specifically, these inhibitors have received approval for treating various hematopoietic cancers, such as cutaneous T‐cell lymphomas. 47 Our findings support the utility of HDAC2 inhibitors in colorectal treatment. SCA, a powerful and specific HDAC2 inhibitor, has been demonstrated to effectively suppresses tumour progression both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…Recent research from China has confirmed the efficacy and safety of tucidinostat as a maintenance treatment for patients with PTCL 13. Meanwhile, Japanese phase II studies of tucidinostat10 and romidepsin14 indicate comparable overall response rate and progression-free survival, but their safety profiles appear to be somewhat different. Both drugs commonly induce haematological toxicity, while tucidinostat has a lower incidence of non-haematological side effects such as nausea, vomiting, constipation, anorexia and fatigue when compared with romidepsin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tucidinostat (formerly known as chidamide), a novel oral HDAC inhibitor that selectively targets class I and class IIb HDACs, received approval from the Chinese Food and Drug Administration in 20149 and from the Japanese Ministry of Health, Labour, and Welfare in 202110 for the treatment of R/R PTCL. Furthermore, several clinical trials with tucidinostat are currently ongoing in the USA, as monotherapy or in combination with other therapies, for both haematological and solid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…• Tucidinostat in R/R PTCL (n = 46), ORR 46%, ORR 88% in AITL, median DOR 11.5 months 112 Hypomethylating agent…”
Section: Epigenomic Mutations Hdac Inhibitormentioning
confidence: 99%